Prevalence and associated positive psychological variables of anxiety and depression among patients with central nervous system tumors in China: a cross‐sectional study. Issue 2 (13th April 2016) - Bao, Yijun; Li, Lizhuo; Guan, Yanlei; Wang, Wei; Liu, Yan; Wang, Pengfei; Huang, Xiaolong; Tao, Shanwei; Wang, Yunjie
Abstract: Background: Anxiety and depression have been identified as common psychological distresses faced by the majority of patients with cancer. However, no studies have investigated the relationship between positive psychological variables (hope, optimism and general self‐efficacy) and anxiety and depression among patients with central nervous system (CNS) tumors in China. Our hypothesis is that the patients with higher levels of hope, optimism or general self‐efficacy have lower levels of anxiety and depression when encountered by stressful life events such as CNS tumors. Methods: Questionnaires, including the Hospital Anxiety and Depression Scale, the Herth Hope Index, the Life Orientation Scale‐Revised and the General Self‐Efficacy Scale, and demographic and clinical records were used to collect information about patients with CNS tumors in Liaoning Province, China. The study included 222 patients (effective response rate: 66.1%). Hierarchical linear regression analyses were performed to explore the associations among hope, optimism, general self‐efficacy and anxiety/depression. Results: Prevalence of anxiety and depression were 42.8 and 32.4%, respectively, among patients with CNS tumors. Hope and optimism both were negatively associated with anxiety and together accounted for 21.4% of variance in anxiety. Similarly, hope and optimism both were negatively associated with depression and accounted for 32.4% of variance in depression. Conclusions: The high prevalence of anxiety and depression among patients with CNS tumors should receive more attention in Chinese medical settings. To help reduce anxiety and depression, health care professionals should develop interventions to promote hope and optimism based on patients' specific needs.